Discovery of G Protein-Biased Dopaminergics with a Pyrazolo[1,5-a]pyridine Substructure - Möller, Dorothee; Banerjee, Ashutosh; Uzuneser, Taygun; Skultety, Marika; Huth, Tobias; Plouffe, Bianca; Hübner, Harald; Alzheimer, Christian; Friedland, Kristina; Müller, Christian P.; Bouvier, Michel; Gmeiner, Peter (Journal of Medicinal Chemistry, 2017)
1,4-Disubstituted aromatic piperazines are privileged structural motifs recognized by aminergic G protein-coupled receptors. Connection of a lipophilic moiety to the arylpiperazine core by an appropriate linker represents a promising concept to increase binding affinity and to fine-tune functional properties. In particular, incorporation of a pyrazolo[1,5-a]pyridine heterocyclic appendage led to a series of high-affinity dopamine receptor partial agonists. Comprehensive pharmacological characterization involving BRET biosensors, binding studies, electrophysiology, and complementation-based assays revealed compounds favoring activation of G proteins (preferably G(o)) over beta-arrestin recruitment at dopamine D-2 receptors. The feasibility to design G protein-biased partial agonists as putative novel therapeutics was demonstrated for the representative 2-methoxyphenylpiperazine 16c, which unequivocally displayed antipsychotic activity in vivo. Moreover, combination of the pyrazolo[1,5-a]pyridine appendage with a 5-hydroxy-N-propy1-2-aminotetraline unit led to balanced or G protein-biased dopaminergic ligands depending on the stereochemistry of the headgroup, illustrating the complex structure functional selectivity relationships at dopamine D2 receptors.

Disrupted-in-Schizophrenia 1 (DISC1) Overexpression and Juvenile Immune Activation Cause Sex-Specific Schizophrenia-Related Psychopathology in Rats - Uzuneser, Taygun; Speidel, Jil; Kogias, Georgios; Wang, An-Li; Silva, Maria A. De Souza; Huston, Joseph P.; Zoicas, Iulia; von Hörsten, Stephan; Kornhuber, Johannes; Korth, Carsten; Müller, Christian P. (Frontiers in Psychiatry, 2019)
Synaptic pruning is a critical refinement step during neurodevelopment, and schizophrenia has been associated with overpruning of cortical dendritic spines. Both human studies and animal models implicate disrupted-in-schizophrenia 1 (DISC1) gene as a strong susceptibility factor for schizophrenia. Accumulating evidence supports the involvement of DISC1 protein in the modulation of synaptic elimination during critical periods of neurodevelopment and of dopamine D2-receptor-mediated signaling during adulthood. In many species, synaptic pruning occurs during juvenile and adolescent periods and is mediated by microglia, which can be over-activated by an immune challenge, giving rise to overpruning. Therefore, we sought to investigate possible interactions between a transgenic DISC1 model (tgDISC1) and juvenile immune activation (JIA) by the bacterial cell wall endotoxin lipopolysaccharide on the induction of schizophrenia-related behavioral and neurochemical disruptions in adult female and male rats. We examined possible behavioral aberrations along three major symptom dimensions of schizophrenia including psychosis, social and emotional disruptions, and cognitive impairments. We detected significant gene environment interactions in the amphetamine-induced locomotion in female animals and in the amphetamine-induced anxiety in male animals. Surprisingly, gene environment interactions improved social memory in both male and female animals. JIA alone disrupted spatial memory and recognition memory, but only in male animals. DISC1 overexpression alone induced an improvement in sensorimotor gating, but only in female animals. Our neurochemical analyses detected sex- and manipulation-dependent changes in the postmortem monoamine content of animals. Taken together, we here report sex-specific effects of environment and genotype as well as their interaction on behavioral phenotypes and neurochemical profiles relevant for schizophrenia.
CRIS-Team WoS Importer:2019-04-18

Presynaptic vesicular accumulation is required for antipsychotic efficacy in psychotic-like rats - Uzuneser, Taygun; Weiss, Eva Maria; Dahlmanns, Jana; Kalinichenko, Liubov; Amato, Davide; Kornhuber, Johannes; Alzheimer, Christian; Hellmann, Jan; Kaindl, Jonas; Hübner, Harald; Löber, Stefan; Gmeiner, Peter; et al. (Journal of Psychopharmacology, 2021)
Background: The therapeutic effects of antipsychotic drugs (APDs) are mainly attributed to their postsynaptic inhibitory functions on the dopamine D2 receptor, which, however, cannot explain the delayed onset of full therapeutic efficacy. It was previously shown that APDs accumulate in presynaptic vesicles during chronic treatment and are released like neurotransmitters in an activity-dependent manner triggering an auto-inhibitory feedback mechanism. Although closely mirroring therapeutic action onset, the functional consequence of the APD accumulation process remained unclear. Aims: Here we tested whether the accumulation of the APD haloperidol (HAL) is required for full therapeutic action in psychotic-like rats. Methods: We designed a HAL analog compound (HAL-F), which lacks the accumulation property of HAL, but retains its postsynaptic inhibitory action on dopamine D2 receptors. Results/outcomes: By perfusing LysoTracker fluorophore-stained cultured hippocampal neurons, we confirmed the accumulation of HAL and the non-accumulation of HAL-F. In an amphetamine hypersensitization psychosis-like model in rats, we found that subchronic intracerebroventricularly delivered HAL (0.1 mg/kg/day), but not HAL-F (0.3–1.5 mg/kg/day), attenuates psychotic-like behavior in rats. Conclusions/interpretation: These findings suggest the presynaptic accumulation of HAL may serve as an essential prerequisite for its full antipsychotic action and may explain the time course of APD action. Targeting accumulation properties of APDs may, thus, become a new strategy to improve APD action.
CRIS-Team Scopus Importer:2020-12-11
Keywords: behavior; Haloperidol; presynaptic accumulation; schizophrenia

Role of the mesolimbic dopamine system in relief learning - Mayer, Dana; Kahl, Evelyn; Uzuneser, Taygun; Fendt, Markus (Neuropsychopharmacology, 2018)
The relief from an aversive event is rewarding. Since organisms are able to learn which environmental cues can cease an aversive event, relief learning helps to better cope with future aversive events. Literature data suggest that relief learning is affected in various psychopathological conditions, such as anxiety disorders. Here, we investigated the role of the mesolimbic dopamine system in relief learning. Using a relief learning procedure in Sprague Dawley rats, we applied a combination of behavioral experiments with anatomical tracing, c-Fos immunohistochemistry, and local chemogenetic and pharmacological interventions to broadly characterize the role of the mesolimbic dopamine system. The present study shows that a specific part of the mesolimbic dopamine system, the projection from the posterior medial ventral tegmental area (pmVTA) to the nucleus accumbens shell (AcbSh), is activated by aversive electric stimuli. 6-OHDA lesions of the pmVTA blocked relief learning but fear learning and safety learning were not affected. Chemogenetic silencing of the pmVTA-AcbSh projection using the DREADD approach, as well as intra-AcbSh injections of the dopamine D2/3 receptor antagonist raclopride inhibited relief learning. Taken together, the present data demonstrate that the dopaminergic pmVTA-AcbSh projection is critical for relief learning but not for similar learning phenomena. This novel finding may have clinical implications since the processing of signals predicting relief and safety is often impaired in patients suffering from anxiety disorders. Furthermore, it may help to better understand psychological conditions like non-suicidal self-injury, which are associated with pain offset relief.
EVALuna2:211709

Schizophrenia dimension-specific antipsychotic drug action and failure in amphetamine-sensitized psychotic-like rats - Uzuneser, Taygun; Schindehuette, Magnus; Dere, Ekrem; von Hörsten, Stephan; Kornhuber, Johannes; Groemer, Teja W.; Müller, Christian P. (European Neuropsychopharmacology, 2018)
Schizophrenic patients suffer from various disruptions in their psyche, mood and cognition, most of which cannot be effectively treated with the available antipsychotic drugs. Some dimensions of the schizophrenia syndrome in man can be mimicked in animals by the amphetamine (AMPH)-sensitization-induced psychosis model. Using such a sensitization procedure, we induced a psychosis-like syndrome in rats, measured as a deficit in sensory information processing and memory deficits. We then investigated the possible restorative effects of continuous treatment with haloperidol (HAL), a typical antipsychotic drug, on distinct dimensions of the syndrome. We found that, continuous infusion of a clinically relevant dose of HAL (0.5 mg/kg/day) effectively ameliorated AMPH-sensitization-induced sensorimotor gating disruptions after seven days of treatment. However, the sensory information processing deficit reappeared after prolonged HAL treatment, suggesting a treatment failure in this dimension of the syndrome. HAL had at this dose little beneficial effects on the cognitive deficits. In contrast, a continuously administered low dose of HAL (0.05 mg/kg/day) successfully attenuated cognitive deficits, but aggravated the sensorimotor gating deficit under both short- or long-term treatment conditions. Post mortem neurochemical analysis revealed that the psychotic-like behavior induced by our manipulations might be explained by altered monoamine levels in distinct brain regions. These findings provide evidence for dissociating and dose-dependent HAL treatment action and failure at different dimensions of schizophrenia.
EVALuna2:36090